ACCULTURATION OF JAVANESE CULTURE IN LOCAL INTERPRETATION: STUDY OF KENDURI TRADITION THROUGH THE INTERPRETATION OF AL-IBRIZ BY KH. BISRI MUSTHOFA - Lumah, Diana Durrotul; Nasrullah, Nasrullah (State Islamic University of Datokarama Palu, 2025)
The tradition of funeral feasts is a deeply rooted cultural practice in Javanese Muslim society and reflects the interaction between Islamic teachings and local wisdom. This study examines how KH. Bisri Musthofa’s Tafsir Al-Ibriz interprets verses about death, namely QS. Ali ‘Imran [3]: 185, QS. An-Nisa’ [4]: ​​78, QS. Al-‘Ankabut [29]: 57, QS. Al-Jumu‘ah [62]: 8, and QS. Al-Hasyr [59]: 10, and how these interpretations provide religious meaning to the practice of funerals. Using a qualitative approach and content analysis methods, this study found that Bisri Musthofa applies a contextual and communicative interpretation style by integrating Javanese language, local idioms, and cultural values ​​such as sangkan paraning dumadi, nrimo, and legawa. This interpretation emphasizes the certainty of death, an orientation toward the afterlife, and the importance of prayer and almsgiving for the deceased. The findings of this study indicate that Tafsir Al-Ibriz serves as a dialectical bridge between Islamic teachings and local traditions, allowing kenduri to be understood not merely as a cultural ritual but as a religious expression rooted in Quranic values.